2020
DOI: 10.1111/ijn.12851
|View full text |Cite
|
Sign up to set email alerts
|

How does nursing research differ internationally? A bibliometric analysis of six countries

Abstract: Background: International nursing research comparisons can give a new perspective on a nation's output by identifying strengths and weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Papers on international trends in nursing research involved mainly English-speaking nations (Australia, Canada, Ireland, New Zealand, the United Kingdom, and the United States; Thelwall & Mas-Bleda, 2020) or Asian countries (South Korea, Taiwan, Japan, and Hong Kong; Im et al, 2020). The top five countries in the world in terms of the number of highimpact papers from 2008 to 2018 were the United States, Australia, the United Kingdom, Canada, and Sweden (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Papers on international trends in nursing research involved mainly English-speaking nations (Australia, Canada, Ireland, New Zealand, the United Kingdom, and the United States; Thelwall & Mas-Bleda, 2020) or Asian countries (South Korea, Taiwan, Japan, and Hong Kong; Im et al, 2020). The top five countries in the world in terms of the number of highimpact papers from 2008 to 2018 were the United States, Australia, the United Kingdom, Canada, and Sweden (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Cluster 3, Warshawsky and Cramer (2019) illustrated the nurse manager role preparation and competency, which cited Kuraoka's (2018) findings on fostering competence among nurse managers via an experiential learning‐based programme, and the two papers shared the same keyword of ‘education’. Therefore, keyword analysis can help identify trends in published research topics with the most frequently used keywords denoting the most popular topics (Thelwall & Mas‐Bleda, 2020). In addition, this study found that the fields of study on core competencies that had the highest citation counts mostly belonged to the following main areas: nursing, business economics and public environmental occupational health; for instance, Egbert et al (2019) indicated the importance of fostering nursing informatics core competency in the digital era.…”
Section: Discussionmentioning
confidence: 99%
“…This is intended to enhance the information available and improve the decision-making on both the practice and research of Nursing. Some of these works provide a comprehensive overview of the quantitative research in Nursing ( Thelwall, 2020 ), the disciplinary context ( Pardo et al., 2001 ) or the detailed historic description of literature that explores the bibliometrics of Nursing research ( Kokol, 2019 ).…”
Section: Introductionmentioning
confidence: 99%